Gender differences in family meal frequency and their association with substance use and mental health among middle and high school students - Ting Luo; Sharon E. Cummins; Shu-Hong Zhu; Shu-Hong Zhu (Frontiers Media S.A., 2023)
BackgroundFamily meals are associated with adolescent health outcomes. Studies have reported that girls are less likely than boys to have dinner with their families.PurposeThis study examined gender differences in family meal frequency and the relationship between meal frequency and other health measures, using a large and representative sample of California middle and high school students.MethodsThis study analyzed data from the 2019-2020 California Student Tobacco Survey (159,904 students in grades 8, 10, and 12). Dinner with the family 5-7 times per week was defined as high frequency. Students reported substance use (of tobacco, marijuana, and alcohol) and rated their mental health and happiness in their home life. All analyses were weighted to reflect the California student population.ResultsFewer than half (44.7%) of students reported a high frequency of family meals, with boys more likely than girls and those who identified their gender in another way the least likely to do so (48.3%, 42.2%, 34.0%, respectively). Gender differences persisted across demographics and the quality of family relationships, and were evident as early as eighth grade. Less frequent family meals were associated with poorer mental health (OR = 1.34, 95% CI: 1.29-1.40) and substance use (OR = 1.27, 95% CI: 1.21-1.32), controlling for the effects of demographics and family dynamics.ConclusionGender differences in family meal frequency emerge early in adolescence and persist across demographics and family relationships. Given that family meals play a protective role in an adolescent's life, these gender differences are concerning.